A simplified proof of the Granja-Merle factorization theorem - García Barroso, Evelia R.; Ploski, Arkadiusz (Pontificia Universidad Católica del Perú, 2019)
En [6] Granja provó una generalización del teorema de Merle [7] para curvas polares de ramas planas. El trabajo presenta una prueba de este resultado sin recurrir a la expansion de Hamburger-Noether o secuencias de Apéry (presentes en la prueba original), sino basándonos en el método desarrollado en [4].

In [G] Granja proved a factorization theorem for power series in two variables which generalized the Merle theorem [M] on polar curves. Our aim is to reprove his result without resorting to Hamburger-Noether expansions and Apéry sequences. We base our proof on the method developed by us in [GB-P l].
Keywords: Teorema de factorización; https://purl.org/pe-repo/ocde/ford#1.01.00